2014
DOI: 10.5194/bg-11-123-2014
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic feeding on various organic food sources by the cold-water coral <i>Lophelia pertusa</i>

Abstract: Abstract. The ability of the cold-water coral Lophelia pertusa to exploit different food sources was investigated under standardized conditions in a flume. The tested food sources, dissolved organic matter (DOM, added as dissolved free amino acids), bacteria, algae, and zooplankton (Artemia) were deliberately enriched in 13 C and 15 N. The incorporation of 13 C and 15 N was traced into bulk tissue, fatty acids, hydrolysable amino acids, and the skeleton ( 13 C only) of L. pertusa. Incorporation rates of carbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Sand-filtered (1-2 mm particle size) bottom water from 45 m depth out of the adjacent Koster fjord (salinity 31) was continuously flushed through the aquaria (∼ 1 L min −1 ). Experience at the station and our earlier experiments showed that the sand-filtered water still contains sufficient organic particles, so that no extra food was provided during the acclimation period (Mueller et al, 2014). …”
Section: Sampling Location and Maintenancementioning
confidence: 88%
See 3 more Smart Citations
“…Sand-filtered (1-2 mm particle size) bottom water from 45 m depth out of the adjacent Koster fjord (salinity 31) was continuously flushed through the aquaria (∼ 1 L min −1 ). Experience at the station and our earlier experiments showed that the sand-filtered water still contains sufficient organic particles, so that no extra food was provided during the acclimation period (Mueller et al, 2014). …”
Section: Sampling Location and Maintenancementioning
confidence: 88%
“…Laboratory studies have confirmed the uptake of suspended particles, bacteria, phytoplankton and zooplankton by cold-water corals (Purser et al, 2010; Published by Copernicus Publications on behalf of the European Geosciences Union. 5790 D. van Oevelen et al: Food selectivity and processing by the cold-water coral Lophelia pertusa Mueller et al, 2014;Orejas et al, 2016). Recently, L. pertusa was also shown to take up dissolved organic matter in the form of free amino acids (Gori et al, 2014;Mueller et al, 2014) and to fix inorganic carbon into its biomass, supposedly through chemo-autotrophic activity of associated microbes (Middelburg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adult L. pertusa polyps are opportunistic feeders capable of exploiting different food sources including zooplankton, microalgae (in the form of marine snow, POM), bacteria, and dissolved organic carbon and other nutrients (Mueller et al, 2014). It seems as though the planulae share the opportunistic heterotrophic diet of the adults.…”
Section: Larval Behavior In Response To Foodmentioning
confidence: 99%